If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 4 = 9x + 3 + 3x + 14 Reorder the terms: 4 + 13x = 9x + 3 + 3x + 14 Reorder the terms: 4 + 13x = 3 + 14 + 9x + 3x Combine like terms: 3 + 14 = 17 4 + 13x = 17 + 9x + 3x Combine like terms: 9x + 3x = 12x 4 + 13x = 17 + 12x Solving 4 + 13x = 17 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 4 + 13x + -12x = 17 + 12x + -12x Combine like terms: 13x + -12x = 1x 4 + 1x = 17 + 12x + -12x Combine like terms: 12x + -12x = 0 4 + 1x = 17 + 0 4 + 1x = 17 Add '-4' to each side of the equation. 4 + -4 + 1x = 17 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = 17 + -4 1x = 17 + -4 Combine like terms: 17 + -4 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| 6-y+12y=39 | | 4(X-1)-2=-20+X | | 5(0.3333333333)+(-3)(1-0.3333333333)=x | | x^2+90x=2925 | | 3(x-5)+8(x-5)=20 | | 5p+(-3)(1-p)=(-3)p+1(1-p) | | (2/5)^(3x-2)=4/25 | | Cos63=5/x | | 0.5x/8=35/8 | | ((2)/(5))^((3x-2))=(4)/(25) | | 6x-2=3x-2 | | 4(0.4)+(-2)(1-0.4)=x | | (-243x^10y^5)^(4/5) | | 3x+x-7=2x-5x+4 | | 7÷44/5 | | 4p+(-2)(1-p)=(-2)p+2(1-p) | | -3(1-3)=2(-4x+7) | | 10x+21=35-2x | | 4x^2+y^2+2y-3=0 | | 1/3t-4/3=-(5/4)t-3/2 | | x^2+8x-57=6 | | 8k-6=-(1-3k) | | 3(0.3)+(-1)(1-0.3)=x | | 6x-6=-5x+5 | | 3(0.3)+(-1)(1-0.3)= | | 100+20t+3t^2=0 | | 5x-10=6-x | | -3(1-3)+8(x-3)=6x+7-5x | | mx+bformx+5y=-5 | | -50+12=-38 | | 6(3x-6)=50 | | 8+2(-5+9n)=15+n |